FactGrid: A database for historians - Universität Erfurt (2018)
"FactGrid wants to provide historical research with a platform that is used collectively and remains in development, regardless of the life cycles which individual have to respect. The software is open source and will be widely used in the future — so far the best promise to remain in development in the long run. We aim to offer data the same advantages on FactGrid: We encourage project participants to mark FactGrid datasets to which they contributed as part of their work while we agree to bring data into open circulation under the CC0 license. We have no objections against the further use of FactGrid data in projects on the platform and outside. All editing processes on the platform are versioned and linked to the respective editors. It is expressly in the project interest that user interfaces are created inside and outside the platform, that access FactGrid data freely and innovatively, and that make them usable in a wide variety of project contexts and thus further develop them." [self-description]